2017
DOI: 10.1080/02680939.2016.1276218
|View full text |Cite
|
Sign up to set email alerts
|

Towards social justice in education: contradictions and dilemmas

Abstract: The article builds on prior arguments that research on issues of social justice in education has often lacked constructive engagement with education policymaking, and that this can be partly attributed to a lack of clarity about what a socially just education system might look like. Extending this analysis, this article argues that this lack of clarity is perpetuated by a series of contradictions and dilemmas underpinning 'progressive' debate in education, which have not been adequately confronted. At the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 58 publications
2
43
0
5
Order By: Relevance
“…Mathematics engagement has been reported to be influenced by domain-specific beliefs about the status of the discipline, a perception of how mathematics knowledge is acquired, and opinions on who best acquires it. Recent research has suggested that the discipline of mathematics is perceived by some to be a more prestigious discipline than other domains of learning due the nature and the demand of the knowledge base (Bleazby, 2015;Francis, Mills, & Lupton, 2017). For example, mathematics has a long-established subject matter that emphasises certainty, reliability and absolute truths, in addition, it contains abstract and theoretical concepts that are considered to be intellectually challenging.…”
Section: Perceptions Of Mathematics As a Subject Areamentioning
confidence: 99%
“…Mathematics engagement has been reported to be influenced by domain-specific beliefs about the status of the discipline, a perception of how mathematics knowledge is acquired, and opinions on who best acquires it. Recent research has suggested that the discipline of mathematics is perceived by some to be a more prestigious discipline than other domains of learning due the nature and the demand of the knowledge base (Bleazby, 2015;Francis, Mills, & Lupton, 2017). For example, mathematics has a long-established subject matter that emphasises certainty, reliability and absolute truths, in addition, it contains abstract and theoretical concepts that are considered to be intellectually challenging.…”
Section: Perceptions Of Mathematics As a Subject Areamentioning
confidence: 99%
“…Þannig er erfiðara og erfiðara að tryggja sér aðgengi í þeim skólum sem þykja bestir. Rannsóknir hafa sýnt að félagslegur og menningarlegur bakgrunnur nemenda hefur áhrif á taekifaeri, námsval og námsgengi þeirra (Francis, Mills & Lupton 2017;Reay 2016Reay , 2018. Í íslensku samhengi má nefna rannsókn Magnúsar Þórs Torfasonar og Margrétar Sigrúnar Sigurðardóttur (2017), sem sýndi meðal annars fram á mikilvaegi tengslanets háskóla nema þegar kemur að einkunnum og brotthvarfi.…”
Section: Stjórnmál and Stjórnsýslaunclassified
“…Much critical research has addressed the disparity between central UK government rhetoric on 'closing the disadvantage gap' and the social consequences of educational reforms (eg Ball, 2016;Thompson, McNicholl and Menter, 2016). However, Francis, Mills and Lupton (2017) have argued that research concerned with social justice has often failed to engage with education policymaking. As Apple (2002) pointed out some time ago, the dominance of right wing ideologies and practices in education still need to be challenged.…”
Section: Introductionmentioning
confidence: 99%